2011
DOI: 10.1007/s10562-011-0572-8
|View full text |Cite
|
Sign up to set email alerts
|

Acetalation of Pentaerithritol Catalyzed by an Al-Pillared Saponite

Abstract: Acetalation of pentaerithritol has been carried out in the presence of an Al-pillared saponite. Several carbonyl compounds were used, including aldehydes and ketones. Yields between 72 and 93% were obtained in all cases, except in the case of veratraldehyde where the carbonyl group was blocked. The high conversion could be explained by diffusion effects of intermediates and electronic effects between the reactants in the transition state. The catalyst was found to be active after three cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…1 And acetals/ketals are oen used as synthetic intermediates, and can be used as starting materials in the production of avours, disinfectants and surfactants. 1,2 Some glycerol acetals may also nd applications as benecial fuel additives, especially to boost the low temperature properties of biodiesel fuels. 3,4 Mota 5,6 once reported that solketal, when used as a fuel additive, can effectively increase the octane number of gasoline and reduce emissions resulting from fuel combustion.…”
Section: Introductionmentioning
confidence: 99%
“…1 And acetals/ketals are oen used as synthetic intermediates, and can be used as starting materials in the production of avours, disinfectants and surfactants. 1,2 Some glycerol acetals may also nd applications as benecial fuel additives, especially to boost the low temperature properties of biodiesel fuels. 3,4 Mota 5,6 once reported that solketal, when used as a fuel additive, can effectively increase the octane number of gasoline and reduce emissions resulting from fuel combustion.…”
Section: Introductionmentioning
confidence: 99%
“…1,2-Diacetal is an efficient protecting group for vicinal 1,2-diol units in carbohydrates. Acetonide formation is the commonly used protection for 1,2-( cis )- and 1,3-diols, which have extensively been used in carbohydrate chemistry to selectively mask the hydroxyls of different sugars …”
Section: Introductionmentioning
confidence: 99%
“…Kannan et al . have reported acetalization of pentaerythritol with several carbonyl compounds in the presence of an Al-pillared saponite.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations